Marine Waste Management at the Samudra Mandiri Syariah Cooperative - Faradilla Fadlia; Safrina Safrina (Dedikasi Sosial: Jurnal Pengabdian Masyarakat, 2025)
Gampong Layeun and Pulot, Leupung District, Aceh Besar, Aceh Province, is famous as a producer of salted fish, fish jerky, and other processed fish products. The communities in the two villages took the initiative to establish the Koperasi Samudra Mandiri as a forum for processed seafood entrepreneurs, especially salted fish products, to gather and develop their businesses together. One of the problems faced by this koperasi is the handling of fish waste, which is classified as organic waste and includes fish innards, scales, etc. Apart from that, household waste management remains a problem. Generally, people throw rubbish into their backyard or burn it. The public does not yet know how to manage waste or how to sort organic and inorganic waste. Apart from that, the regional government responsible for waste management, namely Dinas Lingkungan Hidup, has also not reached the final disposal site to provide waste transportation services. To address the waste problem, the Syiah Kuala University (USK) service team provides waste management education to this community group, especially on sorting and processing organic waste. The Service Team and cooperative members also initiated the preparation of village regulations regarding waste management and coordinated with the village government to create a waste bank.